2021
DOI: 10.1038/s41598-021-84529-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in skin microbiome mediated by radiotherapy and their potential roles in the prognosis of radiotherapy-induced dermatitis: a pilot study

Abstract: Radiotherapy-induced dermatitis (RID) is an inflammatory cutaneous disorder that is acquired as an adverse effect of undergoing radiotherapy. Skin microbiome dysbiosis has been linked to the outcomes of several dermatological diseases. To explore the skin microbiota of RID and deduce their underlying impact on the outcome of RID, cutaneous microbiomes of 78 RID patients and 20 healthy subjects were characterized by sequencing V1-V3 regions of 16S rRNA gene. In total, a significantly apparent reduction in bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
0
13
0
1
Order By: Relevance
“…Based on the rarefied OTUs, α and β diversity were calculated using the R package "PhyloSeq." Shannon (also known as Shannon-Weaver index) (Ott et al, 2014;Gabriel et al, 2019), simpson, and invSimpson index (richness and evenness) and richness (observed OTUs, chao1, ACE) (Ramadan et al, 2021) was used to measure alpha-diversity. Biomarker species were identified based on linear discriminant analysis effect size (LefSe).…”
Section: Fecal Sample Collection and 16s Rrna Gene Sequencingmentioning
confidence: 99%
“…Based on the rarefied OTUs, α and β diversity were calculated using the R package "PhyloSeq." Shannon (also known as Shannon-Weaver index) (Ott et al, 2014;Gabriel et al, 2019), simpson, and invSimpson index (richness and evenness) and richness (observed OTUs, chao1, ACE) (Ramadan et al, 2021) was used to measure alpha-diversity. Biomarker species were identified based on linear discriminant analysis effect size (LefSe).…”
Section: Fecal Sample Collection and 16s Rrna Gene Sequencingmentioning
confidence: 99%
“…Increased rates of pathogenic S. aureus and decreased diversity of other microorganisms are consistently reported in atopic dermatitis lesions in comparison to the healthy skin (64)(65)(66)(67). As reported by Ramadan and colleagues (68), cancer patients with RT-induced dermatitis had significant reduction in bacterial diversity (Shannon, Chao1, and observed species) comparison to healthy controls. The delayed recovery or tendency toward the permanence of RT-induced dermatitis were associated with a raised Proteobacteria/Firmicutes ratio as well as the dermotype with overrepresentation of Pseudomonas, Staphylococcus, and Stenotrophomonas.…”
Section: Skin Microbiome In Skin Toxicitiesmentioning
confidence: 71%
“…Patients were included if they were newly diagnosed with grade 2 RISI. The exclusion criterion was systemic topical application of corticosteroids and antibiotics ( Ramadan et al., 2021 ). The clinical characteristics of patients including age, sex, cancer type, and concomitant diseases are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%